Influência do estresse térmico na produção de interferon tau e no estresse oxidativo de embriões bovinos produzidos in vitro - Amaral, Carolina dos Santos (2019)
Pregnancy losses occur at different stages caused by several conditions, however it occurs more frequently in the first 30 days. This decrease becomes more severe when animals are under unfavorable environmental conditions. Factors such as hyperthermia can reduce conception rates around 20-30% when compared to months where animals are under thermal comfort conditions. Therefore, heat stress (HS) is a problem found in the management of dairy cows in the tropics and subtropics, causing production and reproduction losses. The aim of the present study was to evaluate the influence of HS on development, interferon tau production (IFNT) and oxidative stress of bovine embryos produced in vitro. To evaluate the influence of HS on the in vitro production of bovine embryos, an in vitro model of HS was proposed. This model consists of altering the temperature in some specific stages of the embryo production. To induce HS, the temperature was gradually increased from 38.5°C to 40.5°C, where remained for 6 hours. Then, the temperature was gradually decreased until it returned to 38.5°C. The experimental groups were: control; oocytes submitted to HS during in vitro maturation (IVM HS); oocytes submitted to HS during in vitro fertilization (IVF HS); zygotes submitted to HS during the first day of in vitro culture (IVC HS); and embryos submitted to HS during the first three days of in vitro production (IVM + IVF + IVC HS). All groups submitted to HS had cleavage and blastocyst rates decreased, gene and protein expression of IFNT diminished and oxidative stress increased. The number of embryonic cells per blastocyst, number of trophoblastic cells and cell survival genes expression did not differ among groups. Regarding to cellular stress genes, only HSP70 had a difference among groups, showing an increase in all groups submitted to HS. Although HS is widely studied as a limiting factor in reproduction due to the decrease of hormone levels, gametes quality and embryonic viability, it was demonstrated for the first time the decrease in the production of IFNT in embryos submitted to HS in the early days of development.